OPINI PESERTA SELEKSI CALON APARATUR SIPIL NEGARA (ASN) TERHADAP SISTEM COMPUTER ASSISTED TEST (CAT) - Sinaga, Jona Bungaran Basuki (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
The purposes of using Computerized Assisted Test (CAT) system in civil servant selection were to create transparency, objectivity, accountability and efficiency. Some of the problems formulated in this study are how the public opinion of facilities and services; transparency and purity; and the level of difficulty of the CAT system exam questions. This study aims to determine the opinion of civil servant candidates for Bandung District about facilities, transparency and difficulty level of exam questions with the CAT system. The study was conducted in the Gedung Serbaguna Telkom University Bandung Regency. The population is all civil servant candidates who take the exam by CAT system in Bandung Regency in 2018. The number of samples is 100 people. The variables studied were facilities and services; transparency and purity; exam and graduation questions. Descriptive statistical analysis was performed with the help of SPSS 24 software. The results of the study obtained an average opinion of the participants on the facilities and service variables as well as transparency and were above 3 (three). The lowest average participant opinion is an indicator of the difficulty level of the questions (average = 1.91).